A unique hybodontiform skeleton provides novel insights into Mesozoic chondrichthyan life. (13th January 2021) - Stumpf, Sebastian; López‐Romero, Faviel A.; Kindlimann, René; Lacombat, Frederic; Pohl, Burkhard; Kriwet, Jürgen
Abstract: Asteracanthus was one of the most common Mesozoic hybodontiform chondrichthyans, given that remains traditionally referred to this genus have been reported almost worldwide from Middle Triassic to Late Cretaceous strata so far. Asteracanthus was erected by Louis Agassiz for Late Jurassic fin spines with stellate tubercles. Later, Arthur Smith Woodward synonymized Strophodus, originally introduced by Agassiz for distinctive crushing teeth of Triassic–Cretaceous age, with Asteracanthus based on associated teeth and spines from the English Middle Jurassic. This taxonomic scheme has been accepted for more than 130 years until now, although articulated material has never been found. Here, we present a unique hybodontiform skeleton from the German Late Jurassic, displaying a striking combination of characters: tuberculate dorsal fin spines reminiscent of Asteracanthus, and multicuspid teeth that markedly differ from the crushing teeth previously referred to this genus. Using qualitative and quantitative approaches, we compared its fin spines with those that were found in association with Agassiz's Strophodus teeth, providing evidence that Asteracanthus and Strophodus in fact represent two valid genera distinct from all other hybodontiforms. Morphological features that distinguish fin spines of Strophodus from those of all other hybodontiforms include a straight anterior border and distally distributed posterior denticles. These observations led us to present an emended diagnosis for Asteracanthus . Dentally, Asteracanthus shows strong resemblance to Hybodus, but it otherwise lacks a palatobasal process on the palatoquadrate. Therefore, and in the absence of any reliable phylogenetic framework, we recommend treating Asteracanthus as incertae familiae until hybodontiform interrelationships are resolved.